2019
DOI: 10.1155/2019/9185603
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Recurrent Painful Ophthalmoplegic Neuropathy: A Case Where Pregabalin Was Successfully Employed

Abstract: Recurrent painful ophthalmoplegic neuropathy, previously known as ophthalmoplegic migraine, is a rare condition that affects children and young adults. Its cause and classification are still controversial and, consequently, there are no published treatment guidelines or consensus. Glucocorticoids seem to be beneficial for some patients, but there is no established treatment when failure of this therapy occurs. The aim of this study was to report a case where pregabalin was successfully used after failure of gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
0
13
0
1
Order By: Relevance
“…As shown in Table 1, the demographic and medical characteristics of the cases in our clinic along with the reported cases from other studies that were diagnosed as OM or RPON from 2000 to 2020 were reviewed (46,915,1959). From the database, most reported cases were from the USA, India, Japan, and European countries (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 1, the demographic and medical characteristics of the cases in our clinic along with the reported cases from other studies that were diagnosed as OM or RPON from 2000 to 2020 were reviewed (46,915,1959). From the database, most reported cases were from the USA, India, Japan, and European countries (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…The other 67 patients got ophthalmoplegia concurrently or within 1 week after the headache attack (concurrently: Five cases; within one day: 20 cases; 1–4 days: 20 cases; 4–7 days: 22 cases). In one patient, there was a 15-day interval between the headache and the ophthalmoplegia (47). Sixty-one patients reported that they developed ophthalmoplegia during a headache attack (6,9).…”
Section: Resultsmentioning
confidence: 99%
“…16 In the literature, pregabalin was found to be useful in a patient whose headache and ocular paralysis regressed with steroid therapy but recurred with gradual dose reduction, and who was also unresponsive to prophylaxis with beta-blockers, calcium channel blockers, and topiramate. 18 Wang et al 19 reported an adult patient who did not experience an attack with the combination of valproate and flunarizine. Margari et al 7 reported that valproate was used in a pediatric patient with a history of focal seizures and epileptic abnormalities on electroencephalography, and both electroencephalography findings and the attack frequency decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Case reports for corticosteroid‐resistant cases, as defined by return of pain and cranial nerve palsy after withdrawal of corticosteroids, propose a few options. In one case, beta‐blocker eye drops were used with resolution of symptoms 8 . In another corticosteroid‐resistant case, which was also unresponsive to paracetamol and rizatriptan, pregabalin 150 mg daily resulted in resolution of pain within 7 days 9 …”
Section: Evaluation and Discussionmentioning
confidence: 99%
“…In one case, beta-blocker eye drops were used with resolution of symptoms. 8 In another corticosteroid-resistant case, which was also unresponsive to paracetamol and rizatriptan, pregabalin 150 mg daily resulted in resolution of pain within 7 days. 9 After acute management is successful, prevention must also be considered.…”
Section: Treatmentmentioning
confidence: 99%